Flicking technique for microencapsulation of cells in calcium alginate leading to the microtissue formation. (17th February 2016) - Wong, Soon Chuan; Soon, Chin Fhong; Leong, Wai Yean; Tee, Kian Sek
Abstract : Microbeads have wide applications in biomedical engineering field that include drug delivery, encapsulation of biomolecules, tissue padding and tissue regeneration. In this paper, we report a simple, yet efficient, flicking technique to produce microcapsules of calcium alginate at a narrow distribution of size. The system consists of an infusion pump and a customised flicker that taps the syringe needle for dispersing microcapsules of sodium alginate that polymerised in the calcium chloride solution. The flow rate of the syringe pump and the velocity of the flicker were studied to achieve a well controlled and tunable size distribution of microbeads ranging from 200 to 400 μm. At a flow rate of 4 μl/min and flicking rate of 80 rpm, a narrow size distribution of microbeads were produced. Via this technique, HaCaT cells were encapsulated in calcium alginate microbeads that grown into microtissues with a size ranging from 100 to 300 μm after two weeks of culture. These microtissues could be potentially useful for pharmacological application.